Literature Review: Study of the Use of Interactive Multimedia in Mathematics and Natural Sciences Learning in Indonesia - Hartanto, Bayu Sri (Journal of Multimedia Trend and Technology, 2024)
The use of information and communication technology (ICT) in teaching has become an important issue in recent years in order to improve the quality of education. One use of ICT is as a learning tool, namely in the form of interactive multimedia. Learning using interactive multimedia develops on the basis of conventional learning which cannot meet students' learning needs. This interactive multimedia can be a supplement and complement to learning which represents learning resources. Interactive multimedia is multimedia that is equipped with a controller that can be operated by the user, so that the user can choose what they want for the next process. Interactive multimedia has been widely created and used in Mathematics and Natural Sciences learning in Indonesia. In this paper, a literature review study will be carried out on the use of interactive multimedia in learning in the fields of mathematics and natural sciences, to see developments, development methods, weaknesses and the results that have been achieved. On this occasion, the author provides observation results based on evidence through a literature review regarding the extent of multimedia use in learning, especially in the field of exact sciences such as mathematics and natural sciences.